Biocatalysis and Biomass Conversion in Alternative Reaction Media. Issue 37 (7th July 2016) - Sheldon, Roger A.
Abstract: In this Minireview, the state of the art in the use of ionic liquids (ILs) and deep eutectic solvents (DESs) as alternative reaction media for biocatalytic processes and biomass conversion is presented. Initial, proof‐of‐concept studies, more than a decade ago, involved first‐generation ILs based on dialkylimidazolium cations and non‐coordinating anions, such as tetrafluoroborate and hexafluorophosphate. More recently, emphasis has switched to more environmentally acceptable second‐generation ILs comprising cations, which are designed to be compatible with enzymes and, in many cases are derived from readily available, renewable resources, such as cholinium salts. Protic ionic liquids (PILs), prepared simply by mixing inexpensive amines and acids, are particularly attractive from both an environmental and economic viewpoint. DESs, prepared by mixing inexpensive salts with, preferably renewable, hydrogen‐bond donors such as glycerol and amino acids, have also proved suitable reaction media for biocatalytic conversions. A broad range of enzymes can be used in ILs, PILs and DESs, for example lipases in biodiesel production. These neoteric solvents are of particular interest, however, as reaction media for biocatalytic conversions of substrates that have limited solubility in common organic solvents, such as carbohydrates, nucleosides, steroids and polysaccharides. This has culminated in the recent focus of attention on their use as (co)solvents in the pretreatment and saccharification of lignocellulose as the initial steps in the conversion of second‐generation renewable biomass into biofuels and chemicals. They can similarly be used as reaction media in subsequent conversions of hexoses and pentoses into platform chemicals. Abstract : Medium well done : Second‐generation protic ionic liquids (PILs) and deep eutectic solvents (DESs) have emerged in the last decade as environmentally attractive reaction media for biocatalytic processes. These solvents are of particular interest as reaction media for biocatalytic conversions of substrates that have limited solubility in common organic solvents, such as carbohydrates, nucleosides, steroids, and polysaccharides.